An interdisciplinary approach to inhospital stroke improves stroke detection and treatment time. (27th April 2019) - Manners, Jody; Khandker, Namir; Barron, Adam; Aziz, Yasmin; Desai, Shashvat M; Morrow, Benjamin; Delfyett, William T; Martin-Gill, Christian; Shutter, Lori; Jovin, Tudor G; Jadhav, Ashutosh P
Abstract : Background: Inhospital stroke (IHS) is associated with high morbidity and mortality, likely related to multiple factors, including delayed time to recognition, associated comorbidities, and initial care from non-stroke trained providers. We hypothesized that guided revision of a formalized 'stroke code' system can improve diagnosis and time to thrombolysis and thrombectomy. Methods: IHS activations occurring at a comprehensive stroke center between 2013 and 2016 were retrospectively analyzed to guide revisions of an established stroke code protocol to improve provider communication and time to imaging, reduce stroke mimic rate, and improve the use of parallel processing. After protocol implementation, we prospectively collected data between 2016 and 2017 for comparison with the pre-implementation group, including diagnostic accuracy and relevant time points (code call to examination, examination to imaging, and imaging to intervention). We report descriptive statistics for comparison of patient characteristics and time metrics (time to imaging and reperfusion after IHS activation). Multivariable regression analysis was performed to identify independent predictors of stroke mimics and time metrics. Results: There were 136 cases in the pre-implementation group and 69 in the post-implementation group. A reduction in stroke mimics (52% vs 33%, P=0.01) occurred after protocol initiation. Mean time to imaging after stroke code call was 7.6 min shorter (P=0.026) and mean time from imaging to acute reperfusion therapy was 45.7 vs 19.8 min (P=0.05) in the pre- versus the post-implementation group. Conclusion: Revision of an existing IHS protocol was associated with a lower rate of stroke mimics, and a shorter time to intravenous and intra-arterial intervention.